Peningkatan Agribisnis Tembakau: Seleksi Bibit Unggul Sejak Dini? - Yola, Theodora Merryta; Yuanita, Dielanova Wynni; Dewi, Christine Novita (Jurnal Social Economic of Agriculture, 2023)
This study intends to enhance the process of agribusiness in tobacco in Indonesia starting from decision-making to selecting tobacco seeds (superior and non-superior) until the final result of agribusiness in tobacco. This research analyzes the total costs required in the process of tobacco cultivation until the selling through tobacco collectors. The methods used are interviews and observations of 10 tobacco farmers in Kapencar village of Wonosobo regency as well as 2 tobacco collectors. The researcher conducts interviews with 5 farmers who use superior seeds and the rest who do not. The findings of this study show that the use of superior seeds results in lower cost and the profit of superior seeds is higher than that of non-superior seeds. The use of superior seeds is able to improve the quality of tobacco produced by farmers, as well as the quality of tobacco in Indonesia.